RET Fusion as a Novel Driver of Medullary Thyroid Carcinoma - Grubbs, Elizabeth G. (J Clin Endocrinol Metab, 2015)
INTRODUCTION: Oncogenic RET tyrosine kinase gene fusions and activating mutations have recently been identified in lung cancers, prompting initiation of targeted therapy trials in this disease. Although RET point mutation has been identified as a driver of tumorigenesis in medullary thyroid carcinoma (MTC), no fusions have been described to date. OBJECTIVE: We evaluated the role of RET fusion as an oncogenic driver in MTC. METHODS: We describe a patient who died from aggressive sporadic MTC < 10 months after diagnosis. Her tumor was evaluated by means of next-generation sequencing, including an intronic capture strategy. RESULTS: A reciprocal translocation involving RET intron 12 was identified. The fusion was validated using a targeted break apart fluorescence in situ hybridization probe, and RNA sequencing confirmed the existence of an in-frame fusion transcript joining MYH13 exon 35 with RET exon 12. Ectopic expression of fusion product in a murine Ba/F3 cell reporter model established strong oncogenicity. Three tyrosine kinase inhibitors currently used to treat MTC in clinical practice blocked tumorigenic cell growth. CONCLUSION: This finding represents the report of a novel RET fusion, the first of its kind described in MTC. The finding of this potential novel oncogenic mechanism has clear implications for sporadic MTC, which in the majority of cases has no driver mutation identified. The presence of a RET fusion also provides a plausible target for RET tyrosine kinase inhibitor therapies.